OP05 Outcome of induction therapy with vedolizumab in children: Results from the prospective, multi-centre VEDOKIDS study. (21st January 2022) - Shavit, Z; Stein, R; Aloi, M; Ledder, O; Focht, G; Urlep, D; Hyams, J; Broide, E; Vais, B; Levine, J; Shouval, D; Matar, M; et al.
Abstract: Background: Limited data are available on the use of Vedolizumab (VDZ) in paediatric Crohn's Disease (CD) and Ulcerative Colitis (UC). We evaluated the effectiveness and safety of VDZ to induce remission at week 14 in the prospective, multicenter VEDOKIDS study. Methods: We enrolled children (age 0–18 years) with CD or UC commenced on VDZ with a standardized dosing of 177mg/BSA up to 300mg at 0, 2, 6 and q8 weeks thereafter. Non-responders had their dose escalated to q4wks at the discretion of the local physician. Explicit demographic, clinical and safety data were prospectively recorded via REDcap. Clinical remission was defined as steroid- and EEN-free remission (i.e. wPCDAI<12.5 or PUCAI<10) without the need for new medications. Complete remission was defined as clinical remission with normal CRP and ESR. Predictors of response were explored by Logistic regression. Results: 128 children were enrolled, 60 (47%) with CD, and 68 (53%) with UC (58 (45%) males, mean age 13.8±3.6, 93 (73%) failed previous anti-TNF, median disease duration 2.3 years (IQR 0.9–4.7)). Using the ITT principle, clinical and complete remission rates for CD at week 14 were 30% and 20%, respectively, and for UC 50% and 38%, respectively (Fig 1). Clinical remission rates of those receiving VDZ as first line biologics versus second line were 57% and 34%, respectively (p=0.019; Fig 2); the corresponding complete remission rates were 49% and 23% (p=0.004). In the UC group, disease activity at baseline measured by the PUCAI predicted clinical remission at week 14 (OR=0.95, 95%CI 0.93–0.98; median baseline PUCAI 15 (IQR 0–30) in those achieving remission and 45 (20–55) in those who did not; p=0.002). ESR (OR=0.94, 95%CI 0.89–0.98; p=0.009) and a trend towards extensive disease (L3 vs. L1 and L2; OR 0.14, 95%CI 0.18–1.036, p=0.054) predicted clinical remission in CD. During the 14 weeks, 113 adverse events (AE) were recorded in 58 children: 28 AEs were possibly related to VDZ, all of which were mild-moderate and only 3 (11%) led to discontinuation of VDZ (leukocytoclastic vasculitis, myalgia and dyspnea). There were 18 serious AEs, only one was graded as possibly related to VDZ (headache). There were 18 non-serious cases (19%) of upper respiratory infections (pharyngitis, tonsilitis, parotitis, and otitis media) and one Campylobacter jejuni which was graded as serious. Conclusion: In this prospective multicenter study, VDZ was safe and effective for inducing remission in a refractory cohort of paediatric IBD, more so in UC. Disease severity and extent at baseline may predict clinical response.